2012
DOI: 10.1039/c2cc33931e
|View full text |Cite
|
Sign up to set email alerts
|

A lateral flow biosensor for detection of single nucleotide polymorphism by circular strand displacement reaction

Abstract: A lateral flow biosensor for detection of single nucleotide polymorphism based on circular strand displacement reaction (CSDPR) has been developed. Taking advantage of high fidelity of T4 DNA ligase, signal amplification by CSDPR, and the optical properties of gold nanoparticles, this assay has reached a detection limit of 0.01 fM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 17 publications
0
16
0
Order By: Relevance
“…The limit of detection (LOD) of the assay was 0.01 fM and the quantitative analysis was based on the readout of optical density of AuNPs at the test line using a portable strip reader. Xiao et al reported a lateral flow nucleic acid bioassay that made use of AuNPs as labels for visual detection and circular strand displacement polymerase reaction for target amplification [25]. The LOD of the assay was 0.01 fM and the assay was suitable for the detection of human genomic DNA from blood samples.…”
Section: Introductionmentioning
confidence: 97%
“…The limit of detection (LOD) of the assay was 0.01 fM and the quantitative analysis was based on the readout of optical density of AuNPs at the test line using a portable strip reader. Xiao et al reported a lateral flow nucleic acid bioassay that made use of AuNPs as labels for visual detection and circular strand displacement polymerase reaction for target amplification [25]. The LOD of the assay was 0.01 fM and the assay was suitable for the detection of human genomic DNA from blood samples.…”
Section: Introductionmentioning
confidence: 97%
“…Meanwhile, in order to solve the specificity problem associated with a single hairpin probe, it is feasible to design multiple specific hairpin probes for a target with parallel processing. For the detection of a single nucleotide polymorphism, the combination of using high-fidelity T4 DNA ligase with CSDPR has shown good potential in personalized medicine; for example in the detection of cancerrelated mutations and drug-resistant mutations of infectious agents [7].…”
Section: Specificity and Sensitivitymentioning
confidence: 99%
“…As a result, AuNPs have been extensively explored for biosensing [66], imaging [67], and photothermal cancer therapy [68]. The ability to pegylate AuNPs allows them to preferentially accumulate in tumors via the EPR effect [69].…”
Section: Synthesis Of Hybrid Nanomaterialsmentioning
confidence: 99%